2011
DOI: 10.1258/ar.2011.100361
|View full text |Cite
|
Sign up to set email alerts
|

Rarity of isolated pulmonary embolism and acute aortic syndrome occurring outside of the field of view of dedicated coronary CT angiography

Abstract: As isolated PE, AAS, and significant non-cardiac pathology outside of the DCTA FOV rarely occur, DCTA may replace TRO in the evaluation of patients with non-specific acute chest pain and a low pre-test probability of PE or aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For these reasons, Lee et al suggested that the use of dedicated coronary CT angiography (DTCA), instead of a TRO protocol, is equally safe when triaging patients with nonspecific acute chest pain. 4 Pulmonary transit time needs to be taken into account when performing DTCA in this scenario to avoid a false-negative diagnosis of PE. 5 …”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, Lee et al suggested that the use of dedicated coronary CT angiography (DTCA), instead of a TRO protocol, is equally safe when triaging patients with nonspecific acute chest pain. 4 Pulmonary transit time needs to be taken into account when performing DTCA in this scenario to avoid a false-negative diagnosis of PE. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Surveys have shown a very low yield of unexpected diagnoses in such cases (ie, an aortic dissection in intermediate-risk patients with acute chest pain). 118,119 This result argues against routine use of this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The CCTA DFOV covers the lower two-thirds of the thorax, so theoretically chance of missing isolated upper lobe PTE exists when performing evaluation with z-axis coverage of CCTA. However, considering most of the pulmonary arterial blood flow is directed into the lower lungs, isolated PTE in the upper lobe is expected to be uncommon (10). Isolated PTE in our study were also all located in lower lobes.…”
Section: Discussionmentioning
confidence: 99%